2017
DOI: 10.1002/mp.12640
|View full text |Cite
|
Sign up to set email alerts
|

Low‐dose CT perfusion with projection view sharing

Abstract: Purpose: CT Perfusion (CTP) is a widely used clinical imaging modality. However, CTP typically involves the use of substantial radiation dose (CTDI vol ≥~200 mGy). The purpose of this study is to present a low-dose CTP technique using a projection view-sharing reconstruction algorithm originally developed for dynamic MRI -"K-space Weighted Image Contrast" (KWIC). Methods: The KWIC reconstruction is based on an angle-bisection scheme. In KWIC, a Fourier transform was performed along each projection to form a "k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Besides, the TTP was significantly lower than that in the corresponding healthy side area. The difference was statistically significant ( P < 0.05), indicating that the cerebral perfusion parameters CBF, CBV, MTT, and TTP can predict the occurrence of acute cerebral infarction to a certain extent [ 26 ]. Further analysis showed that the cerebral perfusion parameters CBF, TTP, and MTT in the penumbra were significantly different from the infarct central area and the corresponding contralateral area.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the TTP was significantly lower than that in the corresponding healthy side area. The difference was statistically significant ( P < 0.05), indicating that the cerebral perfusion parameters CBF, CBV, MTT, and TTP can predict the occurrence of acute cerebral infarction to a certain extent [ 26 ]. Further analysis showed that the cerebral perfusion parameters CBF, TTP, and MTT in the penumbra were significantly different from the infarct central area and the corresponding contralateral area.…”
Section: Discussionmentioning
confidence: 99%
“…By converting the CT sinogram into “k-space” data, we can adapt many innovative MRI reconstruction algorithms to preserve high spatial and temporal resolutions of undersampled CT data. In a previous study, we introduced an innovative image reconstruction algorithm based on k-space weighted image contrast (KWIC) [ 23 ], [ 41 ] for radiation dose reduction of CTP [ 24 ]. Our preliminary results showed that KWIC was able to reduce the radiation dose of existing CTP methods by 50–75% without compromising imaging speed or quality.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the central slice theorem, CT sinogram data can be converted to 2D Fourier space (equivalent to k-space in MRI), making it feasible for the adaptation of KWIC to CT perfusion with reduced dose through the sparse sampling of projections followed by view-sharing. In our proof-of-concept study, a specific sparse sampling scheme was employed to achieve up to 75% dose reduction while maintaining both high image quality and quantification accuracy of CTP scans [ 24 ]. However, the implementation of the KWIC algorithm requires rapid-switching pulsed X-ray at pre-specified rotation angles–a hardware capability yet to be implemented by commercial CT vendors.…”
Section: Introductionmentioning
confidence: 99%
“…In total, 248 and 496 images were acquired in the upright (WB) and supine (NWB) positions, respectively. Two-dimensional projection images were reconstructed into a volumetric CT image using a filtered-backprojection method [ 28 30 ] implemented in our in-house reconstruction package, named CONRAD (Radiological Sciences Laboratory, Stanford University, Stanford, CA, USA) [ 31 , 32 ]. A pipeline for the CONRAD software framework for cone-beam imaging is shown in Fig 2 .…”
Section: Methodsmentioning
confidence: 99%